Assessment of published literature regarding skin of color in Pediatric Dermatology. Issue 6 (20th December 2021) - Sun, Mary D.; Wilson, Britney N.; Weitzman, Sarah; Ren, Jennifer; Murrell, Dedee F.; Murase, Jenny E.
Abstract: We sought to analyze the existence of skin of color (SOC)‐related literature in Pediatric Dermatology . To do so, we applied criteria developed by Wilson et al (Assessment of skin of color and diversity and inclusion content of dermatologic published literature: an analysis and call to action. Int J Women Dermatol. 2021;15:26) to categorize SOC articles. We found that Pediatric Dermatology published 28.4% SOC articles in the last three years, higher than the average (16.8%) found across surveyed dermatology journals. Our findings demonstrate opportunity for improvement through the implementation of keyword standardization and continued prioritization of SOC‐related content.